From online to offline sexual offending: Episodes and obstacles. (March 2018) - Fortin, Francis; Paquette, Sarah; Dupont, Benoit
Abstract: Script theory explains how different types of crime may be committed in a particular sequence. While researchers have traditionally been interested in crimes against property and crimes against persons, this study analyzes a new form of crime: sexual crimes committed on the Internet. The objective of the present study was to review the scientific literature and investigate how viewing and creating Child Sexual Exploitation Material (CSEM) can be understood dynamically. It is suggested that a motivated CSEM user, in acquiring new knowledge and techniques, goes through many stages and obstacles that lead ultimately to the contact sexual abuse of children. It is important to note that only a small proportion of individuals who follow the scripts described move on to the next step. The focus here is on the context and not on any causality between the steps, as the latter has not been demonstrated. Specifically, this study looked at the offenders' path from consumption of adult pornography, to consumption of CSEM, to its distribution, to child luring, and, finally, to child sexual abuse and production of CSEM. The limitations and implications of the study are discussed.